Americans' Trust in Health Information Sources: Trends and Sociodemographic Predictors. Issue 8 (November 2019) - Jackson, Devlon N.; Peterson, Emily B.; Blake, Kelly D.; Coa, Kisha; Chou, Wen-Ying Sylvia
Purpose: To assess the public's trust in health information sources (ie, government health agencies, doctors, family/friends, charitable organizations, and religious leaders/organizations) from 2005 to 2015 and identify sociodemographics factors associated with high trust. Design: Cross-sectional. Setting: Health Information National Trends Survey, a US nationally representative publicly available data on health-related knowledge, behaviors, and attitudes. Participants: Data included 5 iterations (2005-2015) of US adults (2005: N = 5586, 2008: N = 7764, 2011: N = 3959, 2013: N = 3185, and 2015: N = 3738). Measures: Outcome variables were high trust in health information sources and independent variables were sociodemographics. Analysis: A descriptive analysis was conducted to track changes in trust over the past decade. The χ 2 and multivariable logistic regression were conducted to assess sociodemographic associations in 2015. Results: Trust in health information across all sources remained stable from 2005 to 2015. Doctors were the most trusted source, followed by government health agencies. Sociodemographics were independently associated with trust. For example, non-Hispanic blacks were more likely to trust charitable organizations (odds ratio [OR] = 2.32, confidence interval [CI] = 1.42-3.79) and religious leaders/organizations (OR = 3.57, CI = 1.20-10.57) compared to non-Hispanic whites. In addition, those with less than high school education (OR = 2.44, CI = 1.32-4.52) were more likely than college graduates to report trust in religious leaders/organizations. Conclusion: Although there are analytic limitations to the specific time periods, the findings demonstrate that public health communication practitioners must consider the role of source credibility among priority populations when disseminating and promoting information.